A interferência da dislexia no processamento da leitura - (:unkn) unknown (Universidade Federal do Pampa, 2021)
Dyslexia is a difficulty in learning to read and write, which is possibly only diagnosed when the child begins his school day. As it is not a disease, but a neurological, congenital and hereditary disorder, which, if diagnosed early and treated correctly, can be overcome, the present work sought, through qualitative research, to investigate what scholars point out in relation to interference. of dyslexia in reading processing, which shows the lack of in-depth studies of dyslexic students in the final years of elementary school, at which time the student starts to have contact with more complex texts. field with Portuguese language teachers to understand the teaching methodologies used in the classroom with dyslexic students already literate in Basic Education, for a possible overcoming of dyslexia disorder, in which it is clear that teachers have knowledge and pedagogical practices suited to each need, as proposed by the Common National Curriculum Base (BRASIL, 2018) in ed Brazilian ucation.
Keywords: Concepções de linguagem; Processamento da leitura; Dislexia; Language concepts.; Reading processing; Dyslexia; CNPQ::LINGUISTICA, LETRAS E ARTES